Resource allocation and MIMO for 4G and beyond - Cavalcanti, Francisco Rodrigo Porto (Springer, 2014)
This book presents the underlying technological breakthroughs that allowed the current state of wireless technology development to evolve. The book focuses on the two lower layers of the ISO/OSI layered model, specifically the physical and data link layers including the media access control sub-layer. These two layers are of particular importance to wireless systems due to the spectrum shortage, the broadcast nature of interference, and time variability in the wireless channel. Topics covered in this book include: radio resource allocation (RRA) for emerging architectures such as Coordinated Multipoint (CoMP) and Device-to-Device communications (D2D); RRA for quality of service control; propagation and transceiver aspects of MIMO systems; and the design and selection of MIMO multiuser precoders. The proposed approaches for RRA and MIMO are applicable to mobile communication standards such as 3GPP's LTE and LTE-Advanced, but also apply further to the continuously evolving wireless access technologies landscape. Each of the book's 11 chapters includes state-of-the-art concepts, introductory sections to the basics, and references for further reading. Several chapters also include technical details related to modern wireless communications technologies along with performance results and case studies. From the foreword: In this book, Professor Cavalcanti and his colleagues share their insights and views on a number of highly relevant research topics related to 4G and 4G technology developments. The content of this book aims at design and optimization of current and emerging cellular systems. Researchers, students and engineers active or interested in the field will find the content useful and are encouraged to share the insights and results. Dr. Göran Klang Ericsson Research Sweden